2015
DOI: 10.2139/ssrn.2649801
|View full text |Cite
|
Sign up to set email alerts
|

Finance and Inclusive Growth

Abstract: The OECD Economic Policy Paper Series is published on the responsibility of the Secretary-General of the OECD. The opinions expressed and arguments employed herein do not necessarily reflect the official views of the Organisation or of the governments of its member countries.Earlier versions of this paper were discussed at the Working Party No. 1 of the OECD Economic Policy Committee, the OECD Economic Policy Committee, the OECD Committee on Financial Markets and seminars of the New Approaches to Economic Chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 108 publications
3
31
0
2
Order By: Relevance
“…It is noteworthy to remind that estimations based on the entire dataset for OECD countries show that whereas an increase in financial intermediation indices has negative effects on growth, stock market expansion is associated with higher growth (Cournède et al ., ).…”
Section: The Literaturementioning
confidence: 97%
See 1 more Smart Citation
“…It is noteworthy to remind that estimations based on the entire dataset for OECD countries show that whereas an increase in financial intermediation indices has negative effects on growth, stock market expansion is associated with higher growth (Cournède et al ., ).…”
Section: The Literaturementioning
confidence: 97%
“…() and Cournède et al . (), reveal the diminishing growth benefits from financial deepening in high income countries.…”
Section: Introductionmentioning
confidence: 99%
“…At higher levels of financial development, capital is more readily available, but its provision may become inefficiently high. Positive and negative channels include the following (Cournède et al , ): More financial development can support higher economic growth through many channels including: ‐ reducing the need for financing projects from own funds; ‐ allocating capital to more productive uses; ‐ monitoring investments more professionally; ‐ providing more insurance, boosting innovation; ‐ facilitating the transmission of monetary policy and ‐ generating productivity gains within the financial sector. On the negative side, too much finance can slow economic growth, particularly by: ‐ misallocating capital by funding projects with too low profitability, for instance, when distortions exist in the tax system or in the form of effective public support for too‐big‐to‐fail banks; ‐ magnifying the distortionary costs of inefficiencies in financial intermediation such as financial sector wage premia (Denk, ) and ‐ heightening the risks of regulatory capture. …”
Section: Financial Development and Economic Growthmentioning
confidence: 99%
“…Source : Cournède et al . (, updated 2016). [Color figure can be viewed at http://wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to textbook consensus, household debt had macroeconomic significance, as Brown (2008) shows. More recently, an OECD report also found that financial sector growth in support of household credit expansion exacerbates income inequality (Cournède, Denk and Hoeller 2015).…”
Section: Inequalitymentioning
confidence: 99%